Ethical evidence and policymaking interdisciplinary and international research. (POLICY PRESS, 2022)
This important book offers practical advice for using evidence and research in policymaking. Covering important policy areas including the GM debate, the environment and Black Lives Matter, each chapter in the book assesses the ethical challenges, the status of evidence in explaining or describing the issue and possible solutions to the problem.